اتجاهات الطلبة الجزائريين نحو الخطاب المسجدي للجامع الاعظم بالجزائر - حسنية لشعل; فطوم بن الشاهد; د/ حسين مساعدي (جامعة عمار ثليجي بالاغواط, 2025)
تهدف الدراسة إلى الكشف عن مدى متابعة الطلبة الجامعيين للخطاب المسجدي للجامع الأعظم بالجزائر، وهذا من خلال تحليل اتجاهاتهم ومواقفهم، نحو الخطاب المسجدي وايضا ترقية وعي المتلقين له، واحداث تغيير في أفكارهم وقناعتهم وكذلك معرفة مستوى التغيير الاجتماعي، الذي يصل اليه الخطاب المسجدي حسب رأي المتلقي لإجراء الدراسة تم الاعتماد المنهج الوصفي المسحي، لكونه الأنسب لرصد اتجاهات وآراء طلبة الجزائريين نحو الخطاب المسجدي للجامع الأعظم بالجزائر ،أجريت على عينة قوامه89مفردة من الطلبة الجامعيين، استخدم في جمع البيانات من هذه العينة أداة استبيان إلكتروني، وبعد مناقشة اجاباتهم على هذا الاستبيان، توصلت الدراسة إلى مجموعة من النتائج اهمها ان طلبة الجامعيين يتابعون الخطب للجامع الأعظم بالجزائر عبر وسائل الرقمية ،وأن الطلبة يميلون إلى خطاب ذو طابع اجتماعي وأخلاقي يتفاعلون بشكل إيجابي معه، كما توصلت الدراسة ان متابعة الخطبة عبر وسائل الحديثة فتحت آفاق جديدة في إيصال رسالة دينية. الكلمات المفتاحية: مسجد- خطاب- اتجاهات – الطلبة الجامعيين Abstract : The study aims to explore the extent to which university students follow the mosque discourse of the Great Mosque of Algiers, by analyzing their attitudes and perceptions towards this discourse, as well as promoting the awareness of its recipients, influencing their thoughts and convictions, and identifying the level of social change achieved by the mosque discourse from the audience's perspective. In order to conduct the study, the descriptive survey method was adopted as it is the most appropriate for observing the attitudes and opinions of Algerian university students towards the mosque discourse of the Great Mosque of Algiers. The study was carried out on a sample consisting of 89 university students. Data were collected from this sample using an electronic questionnaire. After analyzing their responses, the study reached several key findings, the most important of which is that university students follow the sermons of the Great Mosque of Algiers through digital platforms. Moreover, students tend to prefer sermons with a social and moral dimension, to which they respond positively. The study also concluded that following sermons via modern technological means has opened new horizons for conveying the religious message. Keywords : Mosque – Discourse – Attitudes – University Students.
دراسة مسحية على عينة من طلبة كلية العلوم الاسلامية جامعة الاغواط